Biochemical Characteristics of Bone Mineral Metabolism before and throughout the First Year after Kidney Transplantation, Persistent Hyperparathyroidism, and Risk Factors in a Latin Population - Lourdes Balcázar-Hernández; Guadalupe Vargas-Ortega; Baldomero González-Virla; Martha Cruz-López; Raúl Rodríguez-Gómez; Ramón Espinoza-Pérez; Carlos Cuevas-García; Victoria Mendoza-Zubieta (International Journal of Endocrinology)
Bone mineral metabolism disease, which included persistent hyperparathyroidism, is common after successful kidney transplantation (KT) and is related with negative outcomes in kidney transplant recipients. There is a lack of information about bone mineral metabolism, persistent hyperparathyroidism, and its risk factors in Latin kidney transplant recipients (KTRs). Material and Methods: A retrospective study was conducted in 74 patients aged 18–50 years with evolution of 12 months after KT and estimated glomerular filtration rate (eGFR) >60 ml/min; biochemical data of bone mineral metabolism before and at 1, 3, 6, and 12 months of KT were registered. Results. Age was 33 (IQR 27–37) years; 54% (n = 40) were men. Before KT, all patients had hyperparathyroidism, 40% (n = 30) hypocalcemia, 86% (n = 64) hyperphosphatemia, and 42% (n = 31) hyperphosphatasemia. After KT, an increase of calcium and a diminution of PTH, phosphorus, and alkaline phosphatase were corroborated (p=0.001). All patients had hypovitaminosis D (deficiency: 91% (n = 67); insufficiency: 9% (n = 7)); 40% (n = 30) had persistent hyperparathyroidism at 12 months. Hyperphosphatasemia before KT (OR = 4.17 (95% CI: 1.21–14.44); p=0.04), hyperparathyroidism at 6 months (OR = 1.84 (95% CI; 1.67–2.06); p=0.02), hypovitaminosis D at 6 months (OR = 3.94 (95% CI: 1.86–17.9); p=0.01), and hyperphosphatasemia at 6 months (OR = 1.47 (95% CI: 1.07–2.86); p=0.03) were risk factors for persistent hyperparathyroidism at 12 months after KT. Conclusion. Persistent hyperparathyroidism at 6 months, hypovitaminosis D, and hyperphosphatasemia are risk factors for persistent hyperparathyroidism at 1 year of KT in Latin population.